Energy balance and evapotranspiration conditioned by deforestation of a seasonally dry tropical forest (Caatinga): A series of four water seasons - Silva, Thieres George Freire da; Queiroz, Maria Gabriela de; Zolnier, Sérgio; Jardim, Alexandre Maniçoba da Rosa Ferraz [UNESP]; Santos, Wilma Roberta dos; Moura, Magna Soelma Beserra de; Souza, Carlos André Alves de; Steidle Neto, Antonio José; Araújo Júnior, George do Nascimento; Silva, Marcelo José da; Salvador, Kaique Renan da Silva; Silva, Elania Freire da; et al. (Elsevier, 2025)
Changes in land use affect the spatial and temporal variations of surface energy balance components and evapotranspiration in the Caatinga. We aimed to assess the partitioning of energy into latent heat flux (LE) and sensible heat flux (H), as well as actual evapotranspiration (ET), in areas of Caatinga vegetation (CAA) and a deforested area (DEFA) in the Brazilian semi-arid region from 2015 to 2018. Two micrometeorological towers were installed to obtain data during the rainy, dry and transition periods. The energy balance was obtained using the Bowen ratio, based on estimates of daily, monthly and seasonal H and LE fluxes, the latter being used to determine the ET. Higher average values of net radiation (Rn), LE, H and soil heat flux (G) were observed for the CAA landscape, while minimum values were recorded in the DEFA. Mean daily the ET in the CAA and DEFA was 2.19 and 1.97 mm, respectively. Around 23% of the received Rn was used for the LE, 70% for H and 9% for G at the site of the CAA, against 21% of the Rn for LE, 72% for H and 8% for G in the DEFA. Our results further showed that the removal of native vegetation promotes reductions in Rn, air relative humidity, ET and increases the vapour pressure deficit in the DEFA. Greater contributions were observed for H in the dry season, with LE being greater during the rainy season in the Caatinga vegetation area.
Keywords: Bowen ratio; Land-use cover change; Micrometeorology; Semi-arid region